2009
DOI: 10.1021/jp9105844
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Tyrosine in Leu-Enkephalin at a Membrane−Water Interface: An Ultrafast Two-Dimensional Infrared Study Combined with Density Functional Calculations and Molecular Dynamics Simulations

Abstract: The interactions of neuropeptides and membranes play an important role in peptide hormone function. Our current understanding of peptide-membrane interactions remains limited due to the paucity of experimental techniques capable of probing such interactions. In this work, we study the nature of opioid peptide-membrane interactions using ultrafast two-dimensional infrared (2D IR) spectroscopy. The high temporal resolution of 2D IR is particularly suited for studying highly flexible opioid peptides. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…It was concluded that the tyrosine side chain is not embedded in the hydrophobic core of the lipid bilayer. 180 The partitioning of another neuropeptide, 11-residue substance P, into isotropic bicelles was studied by PFG methods. 181 A conformational change of substance P was observed when using bicelles that contain ganglioside GM1.…”
Section: Solution Nmr Studies Of Membrane-associated Peptides and Promentioning
confidence: 99%
“…It was concluded that the tyrosine side chain is not embedded in the hydrophobic core of the lipid bilayer. 180 The partitioning of another neuropeptide, 11-residue substance P, into isotropic bicelles was studied by PFG methods. 181 A conformational change of substance P was observed when using bicelles that contain ganglioside GM1.…”
Section: Solution Nmr Studies Of Membrane-associated Peptides and Promentioning
confidence: 99%
“…For example, the amide I mode of proteins and peptides has been used extensively to probe protein and peptide structure and dynamics using 2D IR spectroscopy. [1][2][3][4][5][6][7][8][9][10][11][12][13] Similarly, the O-H͑D͒ stretching vibration of water, alcohols, and acids has been used to probe hydrogen-bond dynamics. [14][15][16][17][18][19][20][21][22][23] In other cases, external probes can be introduced to the system.…”
Section: Introductionmentioning
confidence: 99%
“…8 Examples of 2D IR studies of biomolecules have been documented in recent literature. [9][10][11][12][13][14][15][16][17][18][19][20] In 2D IR, the anharmonic interaction between two vibrators can be directly shown as off-diagonal anharmonicity, which is an important parameter that may serve as a probe of molecular structure. [21][22][23] Multi-quantum vibrational transitions are very common due to the anharmonic nature of molecular vibrations.…”
Section: Introductionmentioning
confidence: 99%